1998
DOI: 10.1123/ijsn.8.4.356
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Effects of Sodium Citrate Ingestion on High-Intensity Exercise Performance

Abstract: This study examined the effect of sodium citrate ingestion on high-intensity cycling performance in repeated 45-s bouts. Twelve subjects (9 male and 3 female) ingested either a sodium citrate solution (0.3 g ⋅ kg−1 body mass [BM]) or a placebo 90 min prior to exercise. Postingestion blood HCO3 concentrations were significantly higher in the citrate trial (p < .01), but there was no difference in blood pH between trials. Peak power and total work significantly decreased over the five bouts (p < .05) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…The present findings are in agreement with some previous studies that have reported no ergogenic effect on highintensity exercise performance despite significant preexercise alkalosis (9,30,35,43) but are in contrast with others that have reported performance improvements (4,8,18,21,36,42). These latter studies suggest that high-intensity constantwork-rate exercise (95%-125% V O 2max ) may be continued for longer with induced alkalosis when the high-intensity performance bout is preceded by several shorter bouts at the same high-intensity (8,21) or by prolonged submaximal exercise (40 min at 20%-60% V O 2max (18,36)).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The present findings are in agreement with some previous studies that have reported no ergogenic effect on highintensity exercise performance despite significant preexercise alkalosis (9,30,35,43) but are in contrast with others that have reported performance improvements (4,8,18,21,36,42). These latter studies suggest that high-intensity constantwork-rate exercise (95%-125% V O 2max ) may be continued for longer with induced alkalosis when the high-intensity performance bout is preceded by several shorter bouts at the same high-intensity (8,21) or by prolonged submaximal exercise (40 min at 20%-60% V O 2max (18,36)).…”
Section: Discussionsupporting
confidence: 94%
“…Only one study (42) has shown improved time to exhaustion during a single constant-work-rate bout lasting È90 s. In contrast, evidence for any tangible ergogenic effects on ''all-out'' exercise performance resulting from preexercise alkalosis is scant. Bishop et al (4) reported a significant 5% increase in total work done during five 6-s sprints separated by 30-s recoveries, whereas others have shown no performance improvement in repeated 30-s (30), 45-s (43), and 60-s all-out exercise bouts (9). The present results extend these findings in showing that preexercise alkalosis does not improve performance in a single all-out exercise bout lasting 3 min.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This effect is probably due to the presence of three negative charges in the molecule (while bicarbonate ions have only one) which dispose of H + and increase [HCO 3 − ] 57 . This evidence reinforces the hypothesis that timing and dosage of SC ingestion may represent key features to achieve significant functional improvement during exercise and their adequate combination probably lacks when a change in pH is not associated with an ergogenic effect 30,54,58‐63 . In fact, some initial results suggest that to supplement SC at the dose of 0.5 g × kg −1 bw or higher with a timing above 90 minutes is able to improve endurance performance(3 km and 5 km time trials in elite multidisciplinary athletes and well‐trained college runners respectively) in presence of controlled experimental conditions in double‐blind randomized trials 22,45 .…”
Section: Effects On Exercisesupporting
confidence: 59%